You are on page 1of 41

Mathematics

Session

Matrices and Determinants - 3


Session Objectives

1. Singular and Non-singular Matrix


2. Adjoint of a Square Matrix and its Properties
3. Inverse of a Matrix and its Properties
4. Solution of Simultaneous Linear Equations
(Matrix Method)
5. Class Exercise
Singular Matrix

A square matrix A is said to be singular if lAl = 0 .

A is non-singular if A  0.

For Example:

1 1 3
Let A= 1 3 3
5 3 3

A=1(9+9)+1(3+15)+3(3-15)
= 18+18-36
=0

A is a singular matrix .
Non-Singular Matrix
 1 1 1
Let B=  2 1 1
1 2 3

B= 1(-3+2)-1(6-1)+1(-4+1)

= -1 – 5 – 3

= -9 0

B is a non-singular matrix.
Example -1
Find the value of x for which the matrix

x 1 0 
A = 2 -1 1  is singular.
3 4 -2

Solution:

For matrix A to be singular

A =0
x 1 0
 2 -1 1 = 0
3 4 -2
 x  2  4  - 1 -4 - 3  = 0
7
 -2x + 7 = 0  x =
2
Adjoint of a Square Matrix

The transpose of the matrix of cofactors of


elements of a square matrix A is called the
adjoint of A and is denoted by adjA.

adjA = [Cij]T  adjA = C ji 


Adjoint of a Square Matrix
a11 a12 a13 
Let A = a21 a22 a23  , then
a31 a32 a33 

T
C11 C12 C13  C11 C21 C31 
adjA = C21 C22 C23   C12 C22 C32 
C31 C32 C33  C13 C23 C33 

where Cij denotes the cofactor of aij in A.


Example - 2

Find the adjoint of matrix A  


a b

c d

Solution :

A = a b 
c d

C11 = d , C12 =-c

C21 =-b , C22 = a


T
adjA =  d -c 
-b a 

 d -b 
 adjA =  
-c a 
Example - 3
 1 2 1 
Find the adjoint of matrix A   3 1 0 
 0 1 1

Solution:

 1 2 1 
We have A   3 1 0 
 0 1 1

C11  (1  0)  1 , C12  ( 3  0)  3, C13  (3  0)  3


C21  ( 2  1)  3, C22  (1  0)  1 , C23  ( 1  0)  1
C31  (0  1)  1 , C32  (0  3)  3 , C33  (1  6)  5
Solution cont.

T
1 3 3 
 adjA  3 1 1 
 1 3 5 

1 3 1 
 adj A = 3 1 3 
3 1 -5
Properties

A (adjA) = |A| In = (adjA) A

Proof: Let A = [aij] be a square matrix and let Cij be


cofactor of aij in A, then (adjA) = [Cji] for all i, j = 1, 2, ..., n

n  A , if i  j
we know  ir rj 0, if i 
a C  
r 1  j
Properties (Con.)
Therefore, each diagonal element of A (adjA) is
equal to |A| and all non-diagonal elements are equal
to zero.

| A | 0 0 .. 0 
 0 |A| 0 ..0 
i.e. A (adjA) =  = A In
 : : : : 
 
 0 0 0 ..| A |

n  A , if i = j
Similarly, (adjA)A =  ri rj O, if
C a = 
i  j
r=1 

Hence, A (adjA) = |A| In = (adjA)A


Properties (Con.)

2. If A is a non-singular square matrix


of order n, then |adjA| = |A|n – 1
3. If A and B are non-singular square
matrices of same order, then
adj AB = (adjB) (adjA)
4. If A is a non-singular square matrix,
then adj (adjA) = |A|n–2 A.
Example-4
Compute the adjoint of matrix A= 1 2
3 -5 
and verify that A(adj A)=|A|I.

Solution:

We have A = 1 2
3 -5 

C11 =-5 , C12 =-3 , C21 =-2 , C22 =1


T
adjA = -5 -3
-2 1 

= -5 -2
-3 1 
Solution (Con.)
L.H.S. = A  adj.A  = 1 2  -5 -2
3 -5 -3 1 

=  -5-6 -2+2 =  -11 0 


-15+15 -6-5   0 -11

A = -5-6 =-11

R.H.S.= A I=(-11) 1 0 =  -11 0 


0 1  0 -11

 L.H.S = R.H.S

Hence verified.
Example-5
If a matrix A = 
p q
 r s , find det. {A(adjA)}.
Solution:

We have A = p q
 r s 
T
 adjA =  s -r  = -rs -q
p 
-q p  

A(adjA)=  p q  s -q = ps-qr -pq+pq


 r s  -r p   rs-rs -rq+sp 

=(ps-qr) 1 0
0 1

Now, det.{A(adj.A)}=(ps-qr)×1
= ps-qr
Inverse of a Matrix

If a matrix A is non - singular i.e. A  0,


1
then A-1 exists and is given by A-1 = .(adjA)
A

Steps to find inverse of a matrix:

(i) Find out |A| and if A  0 , then the matrix is invertible.


(ii) Find out (adjA).

1
Then A-1 = .(adjA)
A
Example-6
-1 4 2 
Find the inverse of the Matrix A =  2 -1 4
 1 2 3 
Solution:

-1 4 2 
We have A =  2 -1 4
 1 2 3 

-1 4 2
 A = 2 -1 4 = -1 -3 - 8  - 4 6 - 4  +2  4 +1 = 13  0
1 2 3
Solution cont.

T T
C11 C12 C13  -11 -2 5  -11 -8 18
adjA = C21 C22 C23  =  -8 -5 6  =  -2 -5 8 
C31 C32 C33   18 8 -7  5 6 -7 

-11 -8 18
1 1  
Hence, A-1 = .(adjA) = -2 -5 8
A 13  
 5 6 -7 
Properties
(i) A square matrix is invertible if it is non-singular.
(ii) Every invertible matrix possesses a unique inverse.

Proof: Let A be an invertible matrix of


order n x n.
Let B and C be two inverses of A.
Then AB = BA = In
and AC = CA = In
Now AB = In

Multiplying by C C(AB) = CIn


 (CA)B = C In
 In B = C I n Hence, an invertible matrix
possesses a unique inverse.
 B=C
Properties (Con.)

(iii) (AB)–1 = B–1 A–1


or (ABC)–1 = C–1 B–1 A–1

(iv) (AT)–1 = (A–1)T


Example-7
Show that A = 2 -3
3 4  satisfies the equation x - 6x + 17 = 0.
2
 
Hence, find A-1.

Solution:

We have A = 2 -3
3 4 

 A2 = A.A = 2 -3 2 -3 =  4-9 -6-12  =  -5 -18


3 4  3 4  6+12 -9+16 18 7 

A2 -6A+17I2 =  -5 -18 -6 2 -3 +17 1 0


18 7  3 4  0 1

=  -5 -18 - 12 -18 + 17 0 


18 7  18 24   0 17
Solution (Cont.)
 0 0  O Hence, A satisfies the equation x2 - 6x + 17 = 0.
0 0
A2 - 6A + 17I = 0

Multiplying each side by A-1, we get


A-1A2 - 6(A-1A) + 17(A-1I) = A-1.0

(A-1A)A - 6I + 17A-1 = 0 ( A1A  I, A1I  A1 , A1.0  0)

IA - 6I + 17A-1 = 0, 17A-1 = 6I - A
 4 3
-1 1 1  6 0 2 -3  1  4 3  17 17 
A = (6I- A)=  - = =
17 17  0 6  3 4   17 -3 2  3 2
- 
 17 17 
 4 3
 17 17 
Hence, A = 
-1 
 3 2
- 
 17 17 
Example-8
0 1 1 A2 -3I
Find A-1 , if A = 1 0 1. Also show that A =
-1 .
1 1 0 2
Solution:

0 1 1
We have A = 1 0 1
1 1 0

0 1 1
 A = 1 0 1 =0(0-1)-1(0-1)+1(1-0) =1+1 = 2  0
1 1 0

Now,
C11 =-1,C12 =1,C13 =1
T
 -1 1 1  -1 1 1
C21 =1,C22 =-1,C23 =1  adj.A=  1 -1 1 =  1 -1 1
 1 1 -1   1 1 -1 
C31 =1,C32 =1,C33 =-1
Solution cont.  1 1 1
- 2 
 2 2 
1 1  -1 1 1   1 1 1
Hence, A-1 =  adj A  =  1 -1 1  =  - 2

A 2  1 1 -1  2 2 
 
 1 1 1
- 
 2 2 2
 

A2 -3I 1  0 1 1  0 1 1  1 0 0 
Also =  1 0 1  1 0 1  -3 0 1 0 
2 2  1 1 0 1 1 0 0 0 1  
 

1  2 1 1 3 0 0 
=  1 2 1 - 0 3 0 
2  1 1 2 0 0 3 
 

1 -1 1 1 
=  1 -1 1  = A-1
2  1 1 -1
Example-9
2 1 4 5  -1
If A =  and B=   , verify that  AB  = B-1A-1.
5 3 3 4

Solution:

(AB) = 2 1 4 5 
5 3 3 4

= 11 14 
29 37

T
LHS =  AB  =  37 -29 =  37 -14
-1
-14 11  -29 11 
Solution (Cont.)
T
B =  4 -3 =  4 -5
-1
-5 4  -3 4 

T
A =  3 -5 =  3 -1
-1
-1 2  -5 2 

RHS =B-1 A-1 =  4 -5  3 -1 =  37 -14 =LHS


-3 4  -5 2  -29 11 
Solution of Simultaneous Linear
Equations (Matrix Method)
Let the system of 3 linear equations be

a1x +b1y +c1z = d1


a2 x +b2 y +c2 z = d2
a3 x +b3 y + c3 z = d3

This system of linear equation can be written in matrix form as

 a1 b1 c1  x  d1 
a b  
 2 2 c2  y  = d2 
a3 b3 c3  z  d3 

 AX = B ... i
Solution of Simultaneous Linear
Equations (Matrix Method)
The matrix A is called the coefficient matrix of the
system of linear equations.

If A  0 i.e. A is non - singular, then A-1 exists.

Multiplying (i) by A–1, we get

A 1  AX  A 1B

 
 A 1A X  A 1B

B1 A  XI 

1
 X= (adjA)B
A
Important Results

(i) If A is a non-singular matrix, then the system of


equations given by AX = B has a unique solution
given by X = A–1B

(ii) If A is a singular matrix and (adjA)B = 0, then


the system of equations given by AX = B is
consistent with infinitely many solutions.

(iii) If A is a singular matrix and (adjA)B  0, then the


system of equations given by AX = B is
inconsistent.
Example-10
Using matrix method, solve the following
system of linear equations
x + 2y -3z = -4
2x + 3y + 2z = 2
3x - 3y - 4z = 11
Solution:
The given system of equations is
x + 2y - 3z = -4 ...(i)
2x + 3y + 2z = 2 …(ii)
3x -3y - 4z = 11 …(iii)

1 2 -3 x  -4 
or 2 3 2  y  =  2 
3 -3 -4  z  11

 AX = B
Solution (Cont.)

1 2 -3 x  -4 
where A = 2 3 2  , X = y  , B=  2 
3 -3 -4  z  11

1 2 -3
A= 2 3 2
3 -3 -4

1 0 0
= 2 -1 8  Applying C2  C2 - 2C1 and C3  C3 +3C1 
3 -9 5

=1(-5+72)= 67  0

 A-1 exists.

Let Cij be the cofactor aij in A = aij  , then


Solution Cont.
c11 =(-12+6) c12 =- -8-6  c13 =(-6-9)
= -6 =14 =-15

c31 =(4+9) c32 =-(2+6) c33 =(3- 4)


=13 = -8 = -1

c21 =-(-8-9) c22 =(-4+9) c23 =-(-3-6)


=17 =5 =9

c31 =(4+9) c32 =-(2+6) c33 =(3- 4)


=13 = -8 = -1

 -6 14 -15
T
 -6 17 13
 adjA = 17 5 9  =  14 5 -8 
13 -8 -1  -15 9 -1 
Solution (Con.)

-11 1  -6 17 13
 A = .adj A =  14 5 -8 
A 67 -15 9 -1 

Now, X = A-1 B

1  -6 17 13 -4 
 X=  14 5 -8   2 
67 -15 9 -1  11

x  1  201   3 
 y  = -134 = -2
 z  67  67   1 

 x =3 , y =-2 , z =1
Example-11
Using matrices, solve the following
system of equations
x+y+z=6
x + 2y + 3z = 14
x + 4y + 7z = 30

Solution:

The given system of linear equations is


x+y+z=6 …(i)
x + 2y + 3z = 14 …(ii)
x + 4y + 7z = 30 …(iii)

1 1 1 x   6 
or 1 2 3 y  = 14   AX = B
1 4 7  z  30
Solution (Cont.)

1 1 1 x  6
where A = 1 2 3 ; X = y  ; B= 14 
1 4 7  z  30

1 1 1
Now, A = 1 2 3 =1(14-12)-1(7-3)+1(4-2)
1 4 7

=2- 4+2=0

Let Cij be the cofactor aij in A = aij  , then

c11 =(14-12) c12 =-(7-3) c13 =  4-2 


=2 =-4 =2
Solution cont.
c21 =-(7- 4) c22 =(7-1) c23 =-(4-1)
=-3 =6 =-3

c31 =(3-2) c32 =-(3-1) c33 =(2-1)


=1 = -2 =1

T
 2 -4 2  2 -3 1
 adjA =  -3 6 -3  =  -4 6 -2 
 1 -2 1  2 -3 1

 2 -3 1  6  0
and (adjA)B = -4 6 -2 14  = 0 = 0
 2 -3 1 30 0

The given system of equations is consistent with infinitely many solutions.


Solution (Con.)

Putting z = k in first two equations, we get


x+y=6-k
x + 2y = 14 - 3k

1 1  x  6 - k 
or   =   AX = B
1 2 y  14 - 3k 

1 1
A= = 2-1=1  0
1 2
 A-1 exists.
T
2 - 1 2 - 1
 adjA =   = 
-1 1 -1 1
Solution (Con.)
-1 1 2 - 1
A = adjA =  
|A| -1 1

x   2
-1 - 1 6 - k 
Now, X = A B    =   
y  -1 1 14 - 3k 

x  12 - 2k - 14 + 3k  -2 + k 
   = =  
y  -6 + k + 14 - 3k  8 - 2k 
 x = -2 + k and y = 8 - 2k

These values of x, y and z = k also satisfy (iii) equation.

Hence, x = -2 + k, y = 8 - 2k and z = k, where k  R.


Thank you

You might also like